2021
DOI: 10.31014/aior.1992.04.01.326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ICT on Women Entrepreneur Business Performance: Case of Malaysia

Abstract: Women entrepreneur has gained utmost importance in the past few decades in Malaysia due to their significant contribution to the country's economic development. However, few business challenges create a constant obstruction for many women entrepreneurs such as lack of ICT knowledge, time constraint to learn ICT, lack of technological expertise, etc. The present study aims to identify the effect of ICT adoption on business performance and examine how ICT usage helped them handle operational business matters. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Digital technologies play an important role in shaping the business environment for all firms. Growth of firms in the modern time hinges on access and effective implementation of ICT technologies (Isa et al 2021). This implementation of ICT technologies has spurred greater cross-border trade, particularly in the context of regional trade agreements that lower tariffs and other traditional trade barriers, thereby fostering business development, especially for micro, small, and medium enterprises (Bacasmas et al 2022).…”
Section: Digital Technologies and Women Entrepreneurshipmentioning
confidence: 99%
“…Digital technologies play an important role in shaping the business environment for all firms. Growth of firms in the modern time hinges on access and effective implementation of ICT technologies (Isa et al 2021). This implementation of ICT technologies has spurred greater cross-border trade, particularly in the context of regional trade agreements that lower tariffs and other traditional trade barriers, thereby fostering business development, especially for micro, small, and medium enterprises (Bacasmas et al 2022).…”
Section: Digital Technologies and Women Entrepreneurshipmentioning
confidence: 99%
“…Nevertheless, empirical studies have indicated that female entrepreneurs still face performance gaps compared to their male counterparts (Fairlie & Robb, 2009; International Finance Corporation, 2014; Kelley et al, 2017). The practice of women's entrepreneurship in this study refers to the application of various practices by women entrepreneurs aimed at improving business performance (Isa et al 2021). The success of women entrepreneurs' business performance is Effect of Women's Entrepreneurship Practices on Information Communication Technology (ICT) Adoption During the Covid-19 Pandemic: A Case Study in West Sumatra, Indonesia influenced by the adoption of new technologies, such as the internet, which has transformed the way their businesses operate (Agarwal & Lenka 2018).…”
Section: Literature Review Women's Entrepreneurship Practicesmentioning
confidence: 99%
“…Initially, SMEs undertaken by women entrepreneurs were often considered as supplementary income to support their husbands and contribute to household finances. However, with serious dedication, these businesses can become the primary source of household income (Isa et al, 2021).…”
Section: Literature Review Women's Entrepreneurship Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women entrepreneurs have characteristics that set them apart from nonentrepreneur women. Women entrepreneurs in the 21st century seem to combine entrepreneurial characteristics: self-discipline, focus, independence, systematic thinking, empathy, and creativity (Isa et al, 2021). The entrepreneur woman is enthusiastic about dynamism, change, and success.…”
Section: Entrepreneurship and Women Entrepreneursmentioning
confidence: 99%